Leitura compreensiva e crítica: representações de estudantes universitários sobre o ato de ler - Santos, Vania Ribeiro dos (2020)
The present study problematizes reading in the context of the university, with the main objective of understanding the representations of critical and comprehensive reading by students. To this end, it identifies the difficulties faced by students to read academic texts when entering university, as well as analyzing the strategies they use to resolve such difficulties. The theoretical foundations that support the research are supported by the works of Boruchovitch (2018); Chartier (1999); Carlino (2017); Coulon (2008); Freire (2008); Silva (2009); Solé (1998); among others. The locus of the research was the State University of Feira de Santana and the participating subjects were twenty-three students from the first semester 2019.1, from the Pedagogy Degree course. The methodology is based on a qualitative approach and the production of the information took place through reading workshops, using devices such as field diaries and conversation circles. The analysis of the information was made from assumptions of the content analysis (BARDIN, 1977). The results show that the students have representations of comprehensive and critical reading that vary from reading while decoding the word, to reading as a revolutionary and emancipatory act. The production of the information showed that the academics, although they have mastered reading strategies in practice, do not do it consciously. In this sense, the academy, given its social role, has the function of contributing for reading to be transversal in all curricular components, as well as, it is essential that professors assist students in the beginning of graduation, starting from of a systematic planning that discusses conceptions and strategies of reading, as well as reflections about the act of reading in a sociopolitical perspective, with a view to contribute to the formation of understanding and critical readers in the context of Higher Education.